The coryphaei and their satellites: on the problem of artistic anthropology of the “second-class” writer - Вершинина, Наталья (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The paper discusses the underresearched issue of the artistic anthropology of a “second-class” writer as a typological phenomenon, i.e. one which possesses semiotic characteristics independent of particular historical circumstances. Taking as examples Faddei Bulgarin, Mikhail Voskresensky, Alexander Yakhontov and others, the author shows that what they have in common is the kind of artistic reflection, typical of “second-class” writers. This reflection encompasses the following: defining their own place “on the Parnassus” as compared with the classics, interpreting the well-known verbal clichés and the way they construct their image as authors, taking into account certain literary benchmarks. The author of the paper reflects on the ambiguous nature of imitation and on its consequences, which might include an unjustified treatment of the “secondary” cultural phenomena as mere talentless epigonism. The author concludes by defining the position of the “second-class” writers as vulnerable, regardless if they aspire to a high status in the literary hierarchy or just assume the modest role of stewards of the cultural heritage and faithful satellites of the writers perceived as the coryphaei.